The environmental costs of artificial intelligence: the debate in the US (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Artificial intelligence (AI) represents an innovative technology that can offer great opportunities. At the same time, AI raises concerns about the fundamental rights, health and safety of individuals. Only recently, light has begun to be shed on another critical aspect that relates to the environmental costs resulting from the development and large-scale use of complex AI models. This paper explores the environmental impacts of AI, focusing in particular on the energy and water consumption of data centres, as well as the greenhouse gas emissions produced. The analysis focuses primarily on the US context, critically examining current regulations and legislative proposals adopted at the federal and state levels.
Keywords: Artificial intelligence; environmental costs; US context; federal and national legislation; environmental sustainability